Cognitive and Affective Contributions of the Literature Circles Method on the Acquisition of Reading Habits and Comprehension Skills in Primary Level Students - (:unkn) unknown (EDAM, 2011)
This study aimed to examine the effect of literature circles on fourth grade primary students' reading habits and comprehension skills and collected the opinions of students and teachers about the method. In this study, quantitative (pre-test and post-test designs) and qualitative (case study) methods were employed together. The study was conducted on 72 students in the fourth grade of a private school in Istanbul. The data were collected through focus group interviews conducted with teachers and students using Semi-structured interview forms and a reading comprehension scale. The reading comprehension scale was administered as pre-test and post-test. A dependent group's t test was employed for the analysis of the scale scores, and a structured reporting technique was used for the analysis of interview data. The findings of the study showed that the literature circles method improved the reading comprehension skills of students who had low level reading comprehension. It was also found out that students liked reading books by performing different tasks, discussing and cooperating with their friends over a period of time. Students stated that they remembered the book they had read with all the details even two weeks later. The book presentation projects were found beneficial by the students who had prepared them and their audience.
Keywords: Literature Circles; Reading Comprehension; Reading Habit